GENOTYPIC VARIATION IN ENDOSPERM PROTEIN, LYSINE AND TRYPTOPHAN CONTENTS OF NORMAL EXTRA-EARLY MAIZE CULTIVARS AND THEIR QUALITY PROTEIN HYBRIDS UNDER NITROGEN STRESS AND NON-STRESS ENVIRONMENTS - Bello, Omolaran B.; Olawuyi, Odunayo J.; Azeez, Musibau A.; Lawal, Mohammed; Abdulmaliq, Suleiman Y.; Afolabi, Micheal S.; Ige, Sunday A.; Mahamood, Jimoh (Journal of Research (Science), 2025)
Drought and nitrogen (N) tolerance quality protein maize (QPM) could serve as a succor for malnourishment in the Sub-Saharan Africa, and adoption should be intensified where resource poor farmers cannot afford N fertilizer and drought on maize at grain filling stage is frequent. This study compares the quality index, protein, tryptophan and lysine contents of normal extra-early drought-tolerant and their quality protein maize hybrids under sub-optimal and optimal soil N conditions. Four normal drought-tolerant and their respective QPM hybrids were planted under no (0 kg N ha-1), low (30 kg N ha-1) and optimal (90 kg N ha-1) fertilizations at Oke Oyi, Ilorin in the southern Guinea savanna of Nigeria in 2012 and 2013 cropping seasons. The trials were set up in a split plot arrangement with the N rates as main plot and the eight cultivars as sub-plots. Each plot within N levels was four-row, laid out in a randomized complete block design with four replications. The normal cultivars outyielded the QPM versions across N rates with no significance difference. There is a linear increase in all protein qualities with increase in N rates among QPM, while normal maize counterparts had a linear decline with increase in N fertilization. The QPM cultivars also maintained their endosperm protein qualities across N rates. Across N environments, the grain quality characters, such as crude protein, tryptophan, and lysine contents in grain, showed a significant negative relationship with grain yields, which were relatively much stronger under low-N stress. 99TY, TYEEC4, 99TYQ and 20SYNEEWQ have viable traits that could be explored for the development of maize varieties with good grain yield and better protein qualities to improve protein availability in maize based diets and feed for large population of man and livestock.